2007
DOI: 10.1136/bjsm.2006.031617
|View full text |Cite
|
Sign up to set email alerts
|

Near-fatal spontaneous hepatic rupture associated with anabolic androgenic steroid use: a case report

Abstract: Anabolic androgenic steroids are commonly used at high doses by bodybuilders and athletes to enhance physique and improve performance levels. We report a case of spontaneous hepatic rupture with life-threatening haemorrhage associated with a past history of anabolic steroid use.A nabolic androgenic steroids (AAS) are commonly used in high doses by bodybuilders and athletes to enhance physique and improve performance levels. These agents are known to produce changes in various organ systems and cause adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…), hepatic rupture (Patil et al . ) and psychiatric symptoms, such as aggression, recklessness and depression (Pagonis et al . , Lindqvist et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), hepatic rupture (Patil et al . ) and psychiatric symptoms, such as aggression, recklessness and depression (Pagonis et al . , Lindqvist et al .…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, multiple recent controlled studies which used cardiac magnetic resonance imaging (Luijkx et al 2013) or cardiography (Hassan et al 2009, Montisci et al 2012 have found cardiomyopathy in AAS users. In addition to the widespread incidence of cardiac effect, the literature also reports instances of cerebral stroke (Shimada et al 2012), hepatic rupture (Patil et al 2007) and psychiatric symptoms, such as aggression, recklessness and depression (Pagonis et al 2006, Lindqvist et al 2013, Cole et al 2003. Less critical side effects have also been evidenced to include rhabdomyolysis (Farkash et al 2009), lipogranualomatus reaction (Weinreb et al 2010), compartment syndrome and wound dehiscence (Joynes 2010), and abscess (Advisory Council for the Misuse of Drugs (ACMD) 2010, Marquis & Maffulli 2006).…”
Section: Health Risks and Consequencesmentioning
confidence: 99%
“…Use of 17-alpha alkylated AAS (which are orally active) is definitely, albeit rarely, associated with adverse hepatic effects, such as peliosis hepatis (Karasawa et al, 1979), intrahepatic cholestasis (Kafrouni et al, 2007; Sanchez-Osorio et al, 2008), hepatocellular adenomas or carcinomas (Bagia et al, 2000; Gorayski et al, 2008; Socas et al, 2005; Velazquez and Alter, 2004), hepatic angiosarcomas (Daneshmend and Bradfield, 1979; Falk et al, 1979) and spontaneous hepatic rupture (Patil et al, 2007). Adverse hepatic effects with non-17-alpha alkylated AAS, such as testosterone, appear to be extremely rare, but have been described (Carrasco et al, 1985).…”
Section: Specific Long-term Effects Of Aas Usementioning
confidence: 99%
“…AAS use is often discussed as a subset of APED use and the majority of scientific, clinical, and public attention has focused on this single drug class. AASs have obtained notable public interest due to scandals involving professional and Olympic athletes (Catlin et al, 2008; Tsitsimpikou, et al, 2009) as well as tragedies involving suicide/homicide, cardiac events, or other severe psychiatric or medical complications (Cowan, 1994; Dickerman et al, 1995; Hausmann et al, 1998; Huie, 1994; Patil et al, 2007; Peet and Peters, 1995; Santamarina et al, 2008; van Breda et al, 2003). Currently, there is no formal category of AAS or APED misuse in the Diagnostic and Statistical Manual for Mental Disorders-4 th edition ( DSM-IV ; American Psychiatric Association, 1994), but AASs are listed as an “other” substance in the SUD subsection.…”
Section: Introductionmentioning
confidence: 99%